Perancangan Sistem Informasi Akuntansi Persediaan Pada Bengkel Yuwa Motor - Rezagi Meilano; Beni Febrianto (LP2M Politeknik Jambi, 2023)
Yuwa Motoe Workshop is a company engaged in the sale of services and spare parts. Such as car washing, car service, and sales of car equipment and others. The process of data collection of incoming goods and goods out of stock inventory when searching for goods data is still using the manual method. Therefore, this system is expected to help make it easier to record inventory of goods entering goods out of the business of selling services and spare parts. Given the importance of collecting and storing data from each of these sales activities, this accounting information system only requires an internet network to access it. This system is expected to help the Yuwa Motor Workshop business in recording inventory. The result of this research is to produce a web-based inventory information system for incoming and outgoing goods. Provides convenience in providing information on inventory data through incoming goods and outgoing goods using data flow diagrams, DFD, ERD and MySQL for data processing